2018
DOI: 10.1294/jes.29.53
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of a serum albumin removal protocol for use in a proteomic study to identify the protein biomarkers for silent gastric ulceration in horses

Abstract: Silent gastric ulceration occurs without evidence of clinical signs and is common in horses. There is currently no a simple and effective method to diagnose this disease. Proteomics can be used to identify serum biomarkers, but the most abundant serum protein, albumin, could conceal candidate biomarkers. Therefore, it is recommended to remove albumin before a proteomic study; however, there is no specific albumin depletion kit or standard protocol available for horse samples. The objectives of this study were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Several strategies have been shown to be efficient in extracting therapeutic proteins or biomarkers selectively from albumin-rich plasma/serum samples. These strategies include using albumin-depleted plates or columns, 25 trichloroacetic acid (TCA)/acetone, 26 or TCA-isopropanol (IPA). 27 These pre-fractionation protocols have proved effective for removing albumin for the bioanalysis of other retained proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been shown to be efficient in extracting therapeutic proteins or biomarkers selectively from albumin-rich plasma/serum samples. These strategies include using albumin-depleted plates or columns, 25 trichloroacetic acid (TCA)/acetone, 26 or TCA-isopropanol (IPA). 27 These pre-fractionation protocols have proved effective for removing albumin for the bioanalysis of other retained proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no diagnosis marker for EGGD, but attempts have been made to identify serum protein markers for the diagnosis of ESGD. Taharaguchi et al [41] reported the presence of the isoform of alpha 1-antitrypsin as a candidate marker in foals and Poltep et al [34] suggested keratin 1, 6A, and 18 as candidate markers for adult horses.…”
mentioning
confidence: 99%